Long-form Journalism Funding. Theoretical Frames and the Perspective of Media Literacy as Asset. Case Study: Legal Structures of Award-winning Newsrooms in Romania in 2023 and 2024 - BERTIŞAN-POP, Loredana (Studia Universitatis Babeș-Bolyai Ephemerides, 2025)
Financial challenges are not, as literature shows, new lenses when it comes to media. Media landscape has experienced many struggles over the years and while it is diverse and pluralistic in Romania, funding perspectives are still limited. This article aims to understand the legal architecture and financial framework upon which Romanian newsrooms operate and, in particular, if there is or not a discrepancy between award-winning media outlets and high-reach media outlets. Using theoretical frameworks such as the media enterprise concept, journalism as public good, media literacy, and areas of concern for journalism industry as identified in the specialized literature, we conduct a comparative case study of the Superscrieri Award winners (2023, 2024) and the most accessed media outlets as Digital News Report indicates (2023, 2024). Observations show that while non-profit organizations (associations and foundations) are the most dominant among award-winning media outlets, commercial for-profit organizations (SRLs and SAs) are prevalent among readerships. There is hardly any crossover between the two categories, with Libertatea (2023, 2024) and HotNews (2024) being on both lists. Operational and taxation differences highlight the structural vulnerabilities; while NGOs are tax exempt, they are dependent on donors and grants; commercial enterprises are linked to market dependence, being subjects to different taxation. This preliminary study shows that the choice of legal from has an impact on the possibility of producing awarded long format journalistic productions, being linked to operational potential as well as editorial identity.